GAMBARAN ADEKUASI (UREUM & KREATININ), HAEMOGLOBIN, ALBUMIN, SERTA KUALITAS HIDUP PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - setiowati, dwi; Almubarok, Moh Fuad (Journal of Islamic Nursing, 2019)
Haemodialysis may impact on various aspects of patients, including: their daily activities, social roles and psychological aspects. The application of re-use and single-use methods of haemodialysis could be resulting in different quality of life of haemodialysis patients. This study aimed to descript Adequacy, levels of Ureum & Creatinin, Haemoglobin, Albumin and explore quality of life of kidney failure patients undergoing haemodialysis with single-use and re-use methods. This descriptive study used cross sectional approach, recruited 70 kidney failure patients undergoing haemodialysis by consecutive sampling technique. Data collecting used KDQOL-SF 36 questionnaires and medical record, analysis used univariat and  bivariate: T-test and chi-square test to determine the relating factors of quality of life. The result revealed that there were 45,7% respondents with single-use method had good quality of life and 34,30% respondents with re-use method had good quality of life. The result revealed that there were 45,70% respondents with single-use method had Adequated dialysis  and 40% respondents with re-use method had Adequated dialysis. Respondents with single-use method had median of Albumin Level 3,20 gr/dl and 3,16 rg/dl  respondents with re-use method had mean of level Albumin. Respondents with single-use method had mean of Haemoglobin Level 9,38 gr/dl and 9,69 gr/dl respondents with re-use method.   Keywords: Kidney Failure Patients, Single-use and Re-use Haemodialysis Methods,                   Adequacy, Haemoglobin, Albumin, Quality of Life